2020
DOI: 10.1007/s12144-020-00776-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of siblings in the process of forming life satisfaction among young adults – moderating function of gender

Abstract: The main aim of the study was to explore the relationship between life satisfaction and sibling bond quality, with gender playing a moderating role. The sample consisted of 276 young adults with a single biological sibling. The participants completed three questionnaires: a sociodemographic survey, the STQ-Now (quality of the sibling relationship) and the SWLS (level of life satisfaction). No difference was observed between men and women regarding life satisfaction; however, the gender constellation in a sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 79 publications
1
7
0
3
Order By: Relevance
“…We found that older children missed their peers less and this could probably be due to the diffused use of media amongst adolescents during the last decade, regardless of COVID-19 lockdown. In addition, family environment appeared as fundamental for sociality; we found indeed that the presence of siblings reduced the lack of friends, confirming that siblings play a major role in human relationships and that children often perceive them as one of the most important people in life (Szymańska, 2020 ). Children of families with divorced parents missed their friends less, too; however, this could be discussed according to socialization problems and high restraint that may occur in such children (Liu et al, 2000 ), sometimes making them entangled in closer relationships with the single parent and/or developing internalizing attitudes (Cohen & Weitzman, 2016 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We found that older children missed their peers less and this could probably be due to the diffused use of media amongst adolescents during the last decade, regardless of COVID-19 lockdown. In addition, family environment appeared as fundamental for sociality; we found indeed that the presence of siblings reduced the lack of friends, confirming that siblings play a major role in human relationships and that children often perceive them as one of the most important people in life (Szymańska, 2020 ). Children of families with divorced parents missed their friends less, too; however, this could be discussed according to socialization problems and high restraint that may occur in such children (Liu et al, 2000 ), sometimes making them entangled in closer relationships with the single parent and/or developing internalizing attitudes (Cohen & Weitzman, 2016 ).…”
Section: Discussionsupporting
confidence: 63%
“…Socioeconomic disadvantaged situations could also result in impossibility to attend remote classes (Agnelli Foundation, 2020 ), increased anxiety (Vazirani & Bhattacharjee, 2020 ) and violence against children (Cluver et al, 2020 ). The presence of siblings, instead, can affect the availability of resources and spaces for remote learning, but also have an impact on socialization (Szymańska, 2020 ). Family status (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Wprowadzenie W systemie rodzinnym wyjątkowy typ relacji interpersonalnej łączy osoby tworzące rodzeństwa (por. Szymańska, 2020;Walęcka-Matyja, 2018). Do najważniejszych cech tej relacji zalicza się pierwotny charakter oraz długotrwałość.…”
Section: Strona 105unclassified
“…W mniejszym niż dotychczas stopniu są oni skoncentrowani na stosunkach rodzinnych, a bardziej zainteresowani nawiązywaniem nowych, pozarodzinnych relacji. Okres między 20 a 35 rokiem życia uznaje się za czas znaczącej transformacji relacji z rodzeństwem (Szymańska, 2020).…”
Section: Strona 120unclassified
“…Однак лише сиблінги з менш позитивними та інтенсивними стосунками повідомляють про зниження домінантності. Тобто, сиблінги з тісними інтенсивними стосунками можуть не стати більш рівноправними у підлітковому віці (Lindell & Campione-Barr, 2017 (Szymańska, 2020). Серед сестер такі якості сиблінгових стосунків як опозиційність (компонент конфліктності у стосунках) та інтимність (компонент теплоти стосунків) виступають предикторами самотності в сімейному становищі в період ранньої дорослості (Walęcka-Matyja, 2016).…”
unclassified